Community Participation in Development in Baringeng Village, Lilirilau District, Soppeng Regency - Risma Niswaty; Mismadewi Mismadewi; Muh. Darwis; Sitti Hardiyanti Arhas; Sirajuddin Saleh (Jurnal Ilmiah Ilmu Administrasi Publik, 2020)
Community participation is the main asset in achieving the government's program goals. This study aims to determine community participation in development at Baringeng Village, Soppeng regency. Therefore, to find out the objectives of this study, the researcher used descriptive qualitative research. The informants in this study were (7 peoples) using data collection techniques that were carried out through observation, interviews, and documentation. The data obtained from the research results were processed using data analysis techniques consisting of data collection, data reduction, data presentation, and conclusion drawing. The results showed that community participation in development at Baringeng village, Soppeng regency was in the high category. This can be viewed from several indicators, including thought participation, energy participation, property participation, skills participation, and social participation.